Fuzzy‐sliding mode control of nonlinear smart base‐isolated building under earthquake excitation. (18th October 2018) - Ghaffarzadeh, Hosein; Ghaffari, Amir Hossein; Yang, T. Y.
Summary: In this paper, the effectiveness of the fuzzy sliding mode control strategy on three‐dimensional benchmark building with smart base isolation under seismic excitation has been examined. One of the appropriate control theories for such this nonlinear system is the sliding mode control theory; discontinuous sliding mode theory has weakness such as chattering phenomena. In this paper, we used a combination of fuzzy logic and sliding mode theory for the deletion of this defect. The proposed control theory has been scrutinized by applying on lately developed nonlinear three‐dimensional base‐isolated benchmark building. This building because of the three‐dimensional nature, coalescing of lateral and torsional responses, continuity of responses of the superstructure, and base is modeled with three degrees of freedom on every floor. In this building eight actuators assigned only at the base level and in the two directions ( x, y ). In other words, 16 actuators are located underneath the structure. Furthermore, the base isolation system has been modeled by considering lateral coupled equations for a better examination of the performance of the system. The results indicate that reduction of control performance is remarkable. Also, utilizing proposed control theory can decrease the responses of building in two main directions and, particularly, in the rotational degree of freedom.